Biochemical properties of purified polyphenol oxidase from bitter leaf (Vernonia amygdalina) - Olutosin Samuel Ilesanmi; Omowumi Funke Adedugbe; David Adeniran Oyegoke; Rachael Folake Adebayo; Oluwaseun Emmanuel Agboola (Heliyon, 2023)
Polyphenol oxidase which is responsible for oxidative conversion of phenolic compounds to polymers, has continued to attract the attention of scientists. Here, we report the extraction, purification and biochemical properties of polyphenol oxidase (PPO) from bitter leaf (Vernonia amygdalina). The enzyme was purified and concentrated using a non-conventional approach, aqueous two-phase partitioning (ATPS) and the biochemical properties of the purified enzyme were investigated. Substrate specificity studies revealed that the enzyme predominantly exhibits diphenolase activity. The order of substrate preference was catechol > L-DOPA > caffeic acid > L-tyrosine > resorcinol>2-naphthol > phenol. The optimum pH and temperature obtained for the enzyme using catechol as substrate were 5.5 and 50 °C respectively. The estimated Michaelis constant (Km) and maximum velocity (Vmax) for the purified vaPPO using catechol as substrate were 183 ± 5.0 mM and 2000 ± 15 units/mg protein respectively. The catalytic efficiency (Vmax/Km) of the purified vaPPO was 10.9 ± 0.03 min/mg. Na+, K+ and Ba2+ remarkably activated the enzyme and the level of activation was proportional to the concentration. The vaPPO presented stability in the presence of up to 50 mM of the different metal ions tested. In contrast, Cu2+ and NH4+ inhibited the enzyme even 10 mM concentrations. The enzyme was stable in chloroform retaining up to 60% relative activity at 50% (v/v) concentration. There was an increase in the activity (143%) of the enzyme at 30% (v/v) chloroform., revealing that vaPPO could catalyze the substrate more efficiently in 30% (v/v) chloroform. Total loss of enzyme activity was observed at 20% (v/v) concentrations of acetone, ethanol and methanol.In conclusion, the properties of the vaPPO such as its catalysis in the presence of organic solvents, metals and high temperature would be of interest in many biotechnological applications.